A new species of Centropages (Copepoda: Calanoida: Centropagidae) from the central Red Sea based on morphological and molecular evidence - El-Sherbiny, Mohsen M.; Al-Aidaroos, Ali M. (Zootaxa, 2015)
Centropages mohamedi sp. nov. (Copepoda: Calanoida) is described from specimens collected in zooplankton samples off Obhur Creek on the Saudi Arabian coast of the central Red Sea. The new species is most closely related to C. orsinii Giesbrecht, 1889, a species described from the Red Sea and widely distributed in the neritic waters of the Indo-West Pacific region. The new species is mainly distinguished by the female genital double somite, male antennules, male leg 4, and leg 5 of both sexes. DNA sequences of the mitochondrial cytochrome C oxidase subunit one (mtCOI) of the two species differ by 20.8%, supporting their morphology-based identification as distinct species.